2019
DOI: 10.1371/journal.pone.0208291
|View full text |Cite
|
Sign up to set email alerts
|

Development of three-dimensional articular cartilage construct using silica nano-patterned substrate

Abstract: Current strategies for cartilage cell therapy are mostly based on the use of autologous chondrocytes. However, these cells have limitations of a small number of cells available and of low chondrogenic ability, respectively. Many studies now suggest that fetal stem cells are more plastic than adult stem cells and can therefore more efficiently differentiate into target tissues. This study introduces, efficiency chondrogenic differentiation of fetal cartilage-derived progenitor cells (FCPCs) to adult cells can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Despite the fact that controlling cell shape and positioning is a promising approach for cartilage repair, functional cell types and biomaterials are lacking [ 39 ]. Several studies to date have demonstrated that stem cells or progenitor cells derived from human fetal tissue are a promising cell source for cell therapy and tissue engineering [ 40 ]. Because of its high potential for biocompatibility compared to single cells, 3D culture technology has been steadily researched since the 1990s and has recently evolved into 3D spheroids.…”
Section: Application Of 3d Spheroid Culture System To Chondrogenic Di...mentioning
confidence: 99%
“…Despite the fact that controlling cell shape and positioning is a promising approach for cartilage repair, functional cell types and biomaterials are lacking [ 39 ]. Several studies to date have demonstrated that stem cells or progenitor cells derived from human fetal tissue are a promising cell source for cell therapy and tissue engineering [ 40 ]. Because of its high potential for biocompatibility compared to single cells, 3D culture technology has been steadily researched since the 1990s and has recently evolved into 3D spheroids.…”
Section: Application Of 3d Spheroid Culture System To Chondrogenic Di...mentioning
confidence: 99%
“…ADSC spheroids have been suggested to improve cell biological properties, including increasing cell viability and proliferative capacity, stabilizing morphology, and improving metabolic functions, compared to 2D cultures [ 40 ]. In addition, it has been reported that 3D cultures can enhance differentiation markers and anti-inflammatory cytokine gene expression and stimulate ECM secretion [ 14 ]. In this study, the walking performance of 3D hADSC-treated MIA-induced OA rats were significantly improved compared to that of rats administered 2D-cultured hADSCs ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, self-repair of articular cartilage (AC) is difficult because of its low regenerative capacity caused by the lack of blood supply, low cellularity, and a limited number of progenitor cells. Moreover, autograft cartilage cells also have limitations, such as the small number of cells available and low chondrogenic ability [ 14 ]. Stem cell treatment is another approach for the treatment of knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of adhesion molecule expression levels or switching to different types was shown during phases of development (e.g. NCAM) [36] and during differentiation in monolayer/3D culture [37,38]. Furthermore, the importance of cellular adhesion molecules, for interaction with substrate/extracellular matrix (ECM) and force distribution, has been presented (e.g.…”
Section: Discussionmentioning
confidence: 99%